how are you meant to now if you are meant to do 1- phi(z)
the normal case is when the value of z= -... then you have to do 1-phi(z)
but when the value of z= +.... , when do you do 1- phi(z)
any help would be appreciated thanks
S1 normal distribution Watch
- Thread Starter
- 14-04-2013 00:57
- 14-04-2013 02:28
If you have standardised/normalised your data, then it is now in terms of 'x' and you are now working out say
P(Z < z) = phi(z).
Correctly, you said P(Z < -z) = phi(-z) = 1 - phi(z).
Also, if you wanted to do P(Z > z) then you would also do 1 - P(Z < z) = 1 - phi(z).
Why? If you look at your graph of the standard Normal distribution, because it is symmetric, you get that these two values are the same.